BC reads. Adult literacy fundamental English. Reader. 3 - Ivits, Shantel; BC Open Textbook Project; BCcampus (BCcampus, BC Open Textbook Project, 2014)
"This reader contains nine original stories written specifically for adults, and is designed to accompany the BC Reads: Adult Literacy Fundamental English - Course Pack 3. This level 3 reader, one of a series of six readers, is roughly equivalent to grades 3 to 4.5 in the K-12 system. New vocabulary and word patterns are highlighted throughout each story, and then summarized at the end. Font size and line spacing can be adjusted in the online view, and have been enhanced for the print and PDF versions for easier reading. This reader has been reviewed by subject experts from colleges and universities."--BCcampus website.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on version viewed on BCcampus OpenEd website; title from pdf title page.
Keywords: English language -- Study and teaching -- Foreign speakers -- Textbooks; Electronic books